Myocardial infarction with non-obstructive coronary arteries (MINOCA): predictors of long-term outcome. (3rd October 2022) - Abad Romero, R; Fraile Sanz, A; Izquierdo Coronel, B; Olsen Rodriguez, R; Perela Alvarez, C; Galan Gil, D; Espinosa Pascual, M J; Nieto Ibanez, D; Alvarez Bello, M; Martin Munoz, M; Mata Caballero, R; Awamleh Garcia, P; et al.
Abstract: Introduction: Myocardial infarction with non-obstructive coronary arteries (MINOCA) is a heterogeneous clinical entity. There is still limited knowledge about long-term prognosis of MINOCA patients. The aim of this study was to assess the incidence, time-to-event and predictors of mayor adverse cardiovascular events (MACE) in the long-term follow-up. Methods: We carried out an analytical and observational study including all consecutive patients admitted to our hospital with acute myocardial infarction. Patients were classified as obstructive coronary artery disease (MICAD) or MINOCA using the definition of 2020 ESC acute coronary syndrome guidelines. Cardiovascular death, myocardial infarction, stroke and cardiovascular readmission were considered MACE. To determine MINOCA independent predictors, a multivariate analysis with cox regression was carried out in those variables with clinical or statistical relevance. Results: During the studied period, 805 patients were included and 81 (10.1%) of them were diagnosed with MINOCA. Baselines characteristics of MINOCA patients: 53% were men, the mean age was 65±15 years, 67% suffered hypertension, 48% dyslipidemia, 21% mellitus diabetes and 43% were smokers. Follow-up (middle [interquartile range] 38 [19–57] months) was completed in 80 (99%) MINOCA patients and 18 (23%) of them had MACE (8 deaths, 6 myocardial infarctions, 2 strokes and 14 readmissions). The mean time to MACE was 53±2.9 months (Figure 1). Comparing MICAD vs. MINOCA, the 6 years rates of MACE (29% vs. 23%), mortality (12.7% vs. 10.0%), myocardial infarctions (6.5% vs. 7.5%), strokes (2.8% vs. 2.5%) and readmissions (17.5% vs. 24.2%) were similar with no statistically significant differences between MICAD and MINOCA patients. In the multivariate analysis (Table 1) chronic heart failure (HR=18.89; 95% CI 4.94–72.20) and peripheral vascular disease (HR=4.86; 95% CI 1.29–18.36) were independent predictors of MACE in MINOCA patients. The predictive model has a R2 of Nagelkerke of 0.07. Conclusion: This study shows that chronic heart failure and peripheral vascular disease are associated with adverse outcomes in MINOCA patients and appears to be independent predictors of MACE in the long-term follow-up. Those predictors seem to be similar to factors previously shown to predict MACE in MICAD patients. Funding Acknowledgement: Type of funding sources: None.